Cytogenetic Assessment of Blackening Shampoo Used in Temporary Tattoo in the Philippines on Onion (Allium cepa L.) Roots - 2,*, Edcel Jed Samson1 (Asian Journal of Biological and Life Sciences, 2026)
Background: Commercial blackening shampoos containing Para-Phenylenediamine (PPD) are widely used in the Philippines as alternatives to Henna (Lawsonia inermis L.) as a temporary tattoo ink due to their affordability and ease of application. Despite the known allergenic and genotoxic risks of PPD, including chromosomal aberrations and DNA damage, their cytogenetic effects remain understudied locally. Objectives: This study evaluated the cytogenetic impact of a commercial blackening shampoo on onion (Allium cepa) roots. Materials and Methods: Varying concentrations (50 ppm, 300 ppm, 1000 ppm) were used, with distilled water as a negative control and 300 mM H₂O₂ as a positive control. Root length, mitotic index, and chromosomal aberrations were assessed after 48 hr of exposure. Results: Results showed concentration-dependent inhibition: higher concentrations reduced root length and the mitotic index, with the presence of aberrations, including condensed nuclei and vagrant chromosomes. Conclusion: These findings highlight potential health risks from PPD exposure in temporary tattoos, filling gaps in local literature on cytogenotoxicity. The study recommends caution for consumers and further research on animal and human exposure.
Keywords: Allium cepa; Blackening shampoo; Cytogenetic effects; Para-phenylenediamine